2022
DOI: 10.1097/opx.0000000000001897
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Addition of Electrolyte Solutions on the Ferning Patterns of Tears Collected from Normal Eye Subjects

Abstract: SIGNIFICANCEThe current study is the first report to describe the improvement of ferning patterns of human tears using electrolyte solutions. The results can help in the production of new artificial tears to improve the quality of tears.PURPOSEThis study aimed to investigate the effect of the addition of different volumes of various electrolyte solutions on ferning patterns of human tears.METHODSTear samples (20 μL) were collected from the right eye of 13 subjects (5 men and 5 women) aged 19 to 36 years (27.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The dilution effect on the TF patterns of tears was tested in which different proportions of water were added to the tear samples (1:1 to 1:5). No changes were noticed in the TF grades of tears after the addition of water, which is consistent with a previous report [27]. Two masked examiners graded the TF patterns.…”
Section: Tf Testsupporting
confidence: 92%
See 4 more Smart Citations
“…The dilution effect on the TF patterns of tears was tested in which different proportions of water were added to the tear samples (1:1 to 1:5). No changes were noticed in the TF grades of tears after the addition of water, which is consistent with a previous report [27]. Two masked examiners graded the TF patterns.…”
Section: Tf Testsupporting
confidence: 92%
“…It has been reported that the TF grades of tears collected from humans and animals and eye drops improved after the addition of electrolyte solutions [25][26][27]. Generally, divalent electrolytes lead to greater improvement in TF grades compared with monovalent ones [25][26][27].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations